2006
DOI: 10.1080/00140130500475666
|View full text |Cite
|
Sign up to set email alerts
|

Muscle fatigue and endurance during repetitive intermittent static efforts: development of prediction models

Abstract: Localized muscle fatigue has received growing attention as a potential design variable and exposure metric in research towards prevention of musculoskeletal disorders in the workplace. While fatigue during sustained static work has been investigated extensively, effects during tasks comprising work-rest cycles are less clear. Work-rest models for static intermittent work have been presented in several reports, but the applicability is often limited to specific conditions. A study was conducted that facilitated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 45 publications
3
55
0
Order By: Relevance
“…Sundelin (1993) showed beneficial effects of short interruptions on both perceived fatigue and EMG manifestations of muscle fatigue. However, there are also studies, partly in line with our results, that showed no significant responses to passive or active interruptions (Mathiassen 1993;Mathiassen and Winkel 1996;Rissén et al 2002;Iridiastadi and Nussbaum 2006). In line with the findings of Crenshaw, Djupsjöbacka, and Svedmark (2006), we found that active task variation provides more opportunities for the musculoskeletal system to recover, represented as significantly less discomfort development.…”
Section: Task Variation and Conventional Fatigue Parameterssupporting
confidence: 81%
See 1 more Smart Citation
“…Sundelin (1993) showed beneficial effects of short interruptions on both perceived fatigue and EMG manifestations of muscle fatigue. However, there are also studies, partly in line with our results, that showed no significant responses to passive or active interruptions (Mathiassen 1993;Mathiassen and Winkel 1996;Rissén et al 2002;Iridiastadi and Nussbaum 2006). In line with the findings of Crenshaw, Djupsjöbacka, and Svedmark (2006), we found that active task variation provides more opportunities for the musculoskeletal system to recover, represented as significantly less discomfort development.…”
Section: Task Variation and Conventional Fatigue Parameterssupporting
confidence: 81%
“…It might be that task variation was too short to reduce the amount of active motor units (Moritani and Muro 1987). Iridiastadi and Nussbaum (2006) suggested that different muscle compartments or adjacent synergistic muscles are activated over time, which may have led to the absence of changes indicating muscle fatigue in the whole target muscle.…”
Section: Task Variation and Conventional Fatigue Parametersmentioning
confidence: 99%
“…Parameters used in this analysis have been, in addition to amplitude, those that describe mean frequency (MPF) and median frequency (MF) of the power spectrum density function (PSDF) and the number of crossings of the EMG signal through the zero level (Cook et al, 1998;De Luca, 1997;Hägg and Suurkü la, 1991;Masuda et al, 1999;Pincivero et al, 2006;Coorevits et al, 2005;Hummel et al, 2005;Iridastadi and Nussbaum, 2006). Parameters MF and MPF are well accepted as indicators of muscle fatigue at higher levels of muscle contraction (Crenshaw et al, 1997;Gayda et al, 2005;da Silva et al, 2005;Beck et al, 2004;Piscione and Gamet, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Repetitive intermittent static movements cause muscle fatigue, and this correlates with discomfort scores [11]. A study to predict musculoskeletal discomfort using Borg CR10 scales showed that trunk inclination and handling frequency are the major determinants of musculoskeletal discomfort [13].…”
Section: Discussionmentioning
confidence: 99%